The image of the youngest son in Kazakh and Tuvan fairy tales: A comparative analysis - Iskendir, Akkuralay A.; Kenzhekozhayeva, Akbota (The New Research of Tuva, 2026)
The article examines the image of the youngest son in Kazakh and Tuvan fairy tales using as examples tales about three brothers and their younger sibling: “Qaratay”, “The Adventures of Elemes”, and “Baldyr-Beezhek”, “Kheimer-ool and the bull-sized wolf”. The study shows how the hero’s image is formed, reflecting educational, worldview and cultural values, as well as the specificity of its manifestation in different cultural and sociocultural contexts.It is noted that in the tales the youngest son is endowed with positive qualities such as courage, justice and intelligence. Secondary characters or magical objects often come to his aid. These factors determine the typical traits of the main character, enabling him to overcome obstacles that are insurmountable for his elder brothers.Similarities and differences in the images of the youngest son are identified, which are related to the specifics of family hierarchies, social status, value orientations, and the cultural and natural conditions of the respective cultures. The article emphasizes that the image of the “youngest son” demonstrates universal heroic features while adapting to national particularities, thereby reflecting deep ethnocultural and folkloric patterns of the Kazakh and Tuvan peoples.The authors outline prospects for further research by involving comparative material from the folklore of other Turkic and non-Turkic peoples, which will make it possible to study more deeply the genesis of this character in the world literary heritage.
Keywords: Kazakh folklore; Tuvan folklore; fairy tale; youngest son